Pembangunan Berkelanjutan di Tengah Degradasi Lingkungan: Studi Kasus Laman Boenda Tanjungpinang - Dewi, Bunga Amanah; Guwinda, Khoirochy; Rista, Natasya Audrey; Octaviani, Octaviani; Putri, Rizky Fahdilah Aulia (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
Development is synonymous with growth, where the most important achievement in economic development is sustainable economic growth. This research uses a qualitative method with an observation and survey approach using a questionnaire to evaluate the impact of environmental degradation on sustainable development in Laman Boenda Tanjungpinang. The aim of this research is to identify the causes of environmental degradation that affect the number of tourists and their impact on sustainable development and economic factors in the region. The results of the analysis show that environmental degradation reduces tourist attractions and causes damage to public facilities and infrastructure, as well as unstable economic capital hampering development projects. In conclusion, to achieve sustainable development in Laman Boenda Tanjungpinang, efforts to improve the environment and better economic stability are needed.